Bible: the story of the King James Version 1611 - 2011 - Campbell, Gordon (Oxford University Press, 2010)
The King James Version (KJV) of the Bible has long been viewed as the most elegantly written and poetic of the many English translations. Now reaching its 400th anniversary, it remains one of the most frequently used Bibles in the English-speaking world, especially in America. This book offers an authoritative history of this renowned translation, ranging from the Bible's inception to the present day. The text tells the complex story of how this translation came to be commissioned, who the translators were, and how the translation was accomplished